Beyond patient-sharing: Comparing physician- and patient-induced networks - Eva Kesternich; Olaf Rank (Health Care Management Science, 2022)
The sharing of patients reflects collaborative relationships between various healthcare providers. Patient-sharing in the outpatient sector is influenced by both physicians' activities and patients' preferences. Consequently, a patient-sharing network arises from two distinct mechanisms: the initiative of the physicians on the one hand, and that of the patients on the other. We draw upon medical claims data to study the structure of one patient-sharing network by differentiating between these two mechanisms. Owing to the institutional requirements of certain healthcare systems rather following the Bismarck model, we explore different triadic patterns between general practitioners and medical specialists by applying exponential random graph models. Our findings imply deviation from institutional expectations and reveal structural realities visible in both networks.
Keywords: 610; Patient- and physician-induced networks; Outpatient sector; Service complementarity; Closed and open triads; Exponential random graph models